Microbial contamination in open globe injury - Bhala, S; Narang, S; Sood, S; Mithal, C; Arya, AK; Gupta, V (Nepalese Journal of Ophthalmology, 2012)
Introduction: Endophthalmitis is the most dreaded complication of ocular trauma and knowledge of the microbial contaminants is essential to start empirical antibiotic therapy. Purpose: To determine incidence of contamination after open globe injuries (OGI) in our setup and to identify the spectrum of microorganisms contaminating open globe injuries. Material and methods: A prospective study including 50 consecutive eyes of open globe injury over a period of two years was conducted. Intra-operatively, 4 - 5 samples were taken from the inferior conjunctival sac and anterior chamber at the beginning and end of the open globe injury repair. Any abscised tissue or foreign body was also sent for culture sensitivity. A vitreous tap was taken from eyes with posterior segment trauma with signs of endophthalmitis. Results: Microbial cultures were positive in13 eyes (26 %). The microbial spectrum included Aspergillus species in 45.6 %, Alternaria in 15.2 %, Curvularia in 15.2 %, Staphylococcus aureus in 7.6 %, Bacillus species in 7.6 %, and Streptococcus pneumoniae in 7.6 %. Of these 13 eyes, nine eyes developed clinically evident frank endophthalmitis during follow-up. Overall, endophthalmitis developed in 20 eyes (40 %). There was a significant association between the initial contamination and development of endophthalmitis (p < 0.05). 53 % of culture positive cases achieved ambulatory vision compared to 73 % of culturenegative cases. Conclusion: Initial contamination was seen in 26 % of OGI cases. Aspergillus (fungus) was the commonest contaminant. There was a strong correlation between the initial contamination and development of endophthalmitis. Culture-negative cases had a trend towards better final visual outcome than culture-positive cases. Close follow up of cases showing contamination following OGI is recommended. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5857 NEPJOPH 2012; 4(1): 84-89